Visual outcome after cataract surgery in a tertiary eye hospital of Chittagong district, Bangladesh (Asian Journal of Medical and Biological Research, 2019)
To evaluate the visual outcome in patients who have had their cataract surgery in a tertiary hospital of Chittagong district in Bangladesh. This is a clinic-based study of consecutive cataract-operated patients who had age-related cataract with vision less than 6/18 and